Aplikasi Penyusunan Laporan Keuangan Berbasis SAK Etap Pada Bagus Agriseta Mandiri - Mega Indah Puspita Sari; Siti Zubaidah; Setu Setyawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
The purpose of this study is to analyze the arrangement of existing financial report in Bagus Agriseta Mandiri and to conduct the implementation of financial report arrangement that is suitable with SAK ETAP in UKM Bagus Agriseta Mandiri. In this study, the researcher uses case study or field study research that is aimed to learn intensively on the background of problems, situation and the position of the event occurs in nowadays, to solve the problems occurs in company, also the environmental interaction of current social unit in its way (given). The result of this study shows that company only makes loss and profit report, but in its presentation, it still not appropriate with SAK ETAP and financial balance report, cash flow and company equity is not presented yet because of the company less comprehending the standard of arranging financial report. By the existence of SAK ETAP it is expected to create the uniformity in implementing accounting treatment and the presentation of financial report so that it can result appropriate information toward the need of users.